2009
DOI: 10.1586/era.09.74
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw and bisphosphonate use in breast cancer patients

Abstract: It is renowned that breast cancer patients suffer from a number of cancer-related skeletal events, while drugs recently added to the practitioners' quiver, such as aromatase inhibitors, intensify the need to preserve bone mass in this group of patients. Bisphosphonates are potent inhibitors of both normal and pathologic bone resorption. Besides their apoptotic and antiproliferative activity on osteoclasts, bisphosphonates can also exert various effects on macrophages, keratinocytes and fibroblasts. Bisphosphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…We recently provided more solid evidence to support this argument through a longitudinal cohort study of 1,621 patients who received intravenous BP in our institution [3]. Therefore, we argue that root canal treatment is a dental treatment modality that can be safely applied to patients receiving intravenous bisphosphonates [2][3][4]. Moreover, we propose that root canal treatment should be an alternative to avoid dental extractions [4].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…We recently provided more solid evidence to support this argument through a longitudinal cohort study of 1,621 patients who received intravenous BP in our institution [3]. Therefore, we argue that root canal treatment is a dental treatment modality that can be safely applied to patients receiving intravenous bisphosphonates [2][3][4]. Moreover, we propose that root canal treatment should be an alternative to avoid dental extractions [4].…”
mentioning
confidence: 84%
“…Therefore, we argue that root canal treatment is a dental treatment modality that can be safely applied to patients receiving intravenous bisphosphonates [2][3][4]. Moreover, we propose that root canal treatment should be an alternative to avoid dental extractions [4].…”
mentioning
confidence: 97%
“…A comprehensive graphic summary of this hypothesis has been published. 4 Allen and Burr 1 concluded that other important areas related to ONJ surely exist, that the initiation of hypothesisdriven studies is essential to further elucidate the etiopathogenesis of ONJ, and that interest in ONJ within the research community will wane if the field does not move forward. In this context, these hypotheses accommodate important consequences for clinician practice and research.…”
Section: Novel Hypotheses In the Etiopathogenesis Of Bisphosphonate-rmentioning
confidence: 99%
“…4. Reading [4], increasing bisphosphonate accumulation in the skeleton with time may lead to ONJ development. Incidentally, the majority of ONJ cases are reported to occur after administration of over six bisphosphonate doses [5].…”
mentioning
confidence: 99%
“…Future, prospective epidemiological efforts from academic researchers will support or reject the latter argument. Until then, caution should be paid to the preventive measures suggested by various organizations [4] for every patient receiving bisphosphonates.…”
mentioning
confidence: 99%